Descriptive Study of College Student’s Career Adaptability with An Internship Experience - Ameliah, Asti Deasya; Jatnika, Ratna (Goodwood Publishing, 2024)
Purpose: The purpose of this study is to examine career adaptability among college students with internship experience. Research Methodology: This study used a non-experimental design with a quantitative descriptive method. Respondents in this study were 64 college students with internship experience who were chosen by quota sampling technique. Respondents were asked to fill out a questionnaire on the Career Adapt-Abilities Scale with a reliability of 0.948. Results: The results of the study showed that the career adaptability of 76.6% of college students with an internship experience was categorized as high. Furthermore, the profile of each dimension of career adaptability shows that most college students with internship experience also have a high profile in all dimensions. Limitations: The inability to depict the career adaptability profile of respondents based on all the antecedent factors of career adaptability (adaptivity), such as cognitive ability and self-esteem, as well as other factors like educational institution, socioeconomic status, age, and family circumstances. Contribution: The research contributes by offering insights to guide higher education institutions in facilitating students' internship experiences. Additionally, it provides valuable knowledge to students about the importance of developing a comprehensive career adaptability profile. This understanding, which includes various dimensions of career adaptability, helps students prepare for future career challenges and transitions.